LIPID CONTENT OF THE GONAD AND MUSCLE DURING THE MATURATIONCYCLE IN FRESHWATERFISH WALLAGO ATTU (HAMILTON) - SHENDGE, A.N.; PAWAR, B.A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Changes in the lipid content of gonad and muscle of Wallago attu (Ham.) during different phases of maturity cycle were investigated. The results are discussed in the light of lipid utilization in gonadal maturity. During maturation process of gonad, lipid content increased in the gonad while decreased in the muscle. Relatively higher lipid content was recorded in the gonad of both the SCXCS.